Pengaruh Zakat dan Corporate Social Responsibilty terhadap Kinerja Keuangan UKM - Putri Reno Kemala Sari; Eno Ayunda (Program Studi Manajemen FEBM UMRAH, 2023)
This study aims to test whether zakat and corporate social responsibility affect the financial performance of SMEs. If you pay attention to zakat and SMEs, it is carried out by both sharia-based companies and conventional-based companies. In this case the corporate zakat in question is the zakat paid by the company from the total profit that the company generates. This study uses a quantitative method. The sample in this study amounted to 45 respondents obtained by non-probability sampling method with convenience sampling technique. The data obtained was processed using multiple linear analysis techniques through SPSS software. The results of the analysis in this study indicate that (1) the variable quality of zakat has a positive and significant effect on the financial performance of SMEs in Alas Barat District, Sumbawa; (2) The corporate social responsibility variable has a positive and significant effect on the financial performance of SMEs in Alas Barat, Sumbawa Keywords: Zakat, Corporate Social Responsibility, Financial Performance